Pengaruh Water Injection System pada Mesin 100cc Berbahan Bakar LPG Terhadap Konsumsi Bahan Bakar Spesifik dan Temperatur Mesin - Ali, Reynaldi Akbar; Mulyono, Novangga Adi; Aulina, Audha Fitrah (AEEJ : Journal of Automotive Engineering and Vocational Education, 2024)
The number of motorized vehicles in Indonesia is increasing. Therefore, alternative fuels are needed to meet the needs. One of them is LPG (liquified petroleum gas). However, in its application, the engine temperature becomes hotter, making it less efficient, and specific fuel consumption is not optimal. The Water Injection System is one of the additional technologies that can be used to reduce engine heat. This study will compare the results of specific fuel consumption and engine wall temperature with adding a water injection system on a 100cc engine. The data collection results on specific fuel consumption at 3000 RPM without water injection showed the highest figure at 0.0410 (kg/HP.hour), with the addition of a water injection system, it produced 0.0405 (kg/HP.hour). The average engine working temperature without a water injection system was 90.3 0C while adding a water injection system showed 87.8 0C. Jumlah kendaraan bermotor di Indonesia semakin meningkat. Untuk itu diperlukan bahan bakar alternatif untuk memenuhi kebutuhan. Salah satunya adalah LPG (liquified petroleum gas). Namun pada aplikasinya, temperatur mesin menjadi lebih panas, sehingga kurang efisien dan konsumsi bahan bakar spesifiknya tidak optimal. Water injection System adalah salah satu teknologi tambahan yang dapat digunakan untuk mengurangi panas mesin. Penelitian ini akan membandingkan hasil specific fuel consumption dan temperatur dinding mesin dengan penambahan water injectiontion system pada mesin 100cc. Hasil pengambilan data specific fuel consumption pada 3000 RPM tanpa water injection menunjukkan angka tertinggi di 0,0410 (kg/HP.jam) dan dengan penambahan water injection system menghasilkan 0,0405 (kg/HP.jam). Temperatur kerja mesin rata rata tanpa water injection system menunjukkan 90,3 0C sedangkan ketika menambahkan water injection system menunjukkan 87,8 0C.